2022
DOI: 10.3390/ijerph192416568
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Consumer Behavior toward Green Products: A Systematic Literature Review

Abstract: In the last few decades, humans have consumed more resources than in all of previous history. Hence, we are living in times in which the topic of environmental protection is a global concern. The paper aims to conduct a systematic literature review on consumer behavior, as well as identifying the main factors that interfere with consumer behavior toward green products. A total of 37 studies were found and systematized using inclusion and exclusion criteria. The papers were selected only if they featured resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 83 publications
(210 reference statements)
0
26
0
Order By: Relevance
“…Similarly, [76] assessed a positive influence between gender and consumption behaviour. In addition, the study of [2] showed a positive relationship between consumer confidence and green consumption behaviour. Thus, a green marketing policy is essential to stimulate consumer confidence which will act directly on green purchasing behaviour.…”
Section: Discussion: What Are the Prospects For Green Consumption In ...mentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, [76] assessed a positive influence between gender and consumption behaviour. In addition, the study of [2] showed a positive relationship between consumer confidence and green consumption behaviour. Thus, a green marketing policy is essential to stimulate consumer confidence which will act directly on green purchasing behaviour.…”
Section: Discussion: What Are the Prospects For Green Consumption In ...mentioning
confidence: 96%
“…With climate change, biodiversity loss, and deforestation, companies are increasingly sensitive to global environmental issues [1]. These problems require the integration of environmental management into the management system of companies [2,3]. Taking the environment into account has become the mantra of companies wishing to expand their market share and have a competitive advantage in the global market [4].…”
Section: Introductionmentioning
confidence: 99%
“…The marketplace seems to play a crucial role among consumers seeking foods with lower environmental footprints as well. Barbu et al (2022) reported that farmers' markets are preferred marketplaces for "green consumers" because of the local sourcing and sustainability focus of products sold at these outlets. This aligns with the findings of Marques et al (2021), who identified "localness" as a major driver of purchasing at farmers' markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be indicated that consumers have realized the increasing global environmental issues and have understood their responsibility in solving these problems [13,16]. Therefore, consumers' environmental concerns, attitudes, preferences, and awareness have become increasingly significant in the market and in society [17,18].…”
Section: Introductionmentioning
confidence: 99%